PARADOXES OF FIDELITY. Children's Poems by H. Tumanyan Interpreted by B. Akhmadulina. - KUBATIAN, GEORGY (Bulletin of Yerevan University H: Russian Philology, 2019)
The famous Russian poet Bella Akhmadulina, in addition to a number of poems and ballad "Parvana", translated also Hovhannes Tumanian՛s poems for the children. The article analyzes these translations. It is noted that Akhmadulina often don’t observe the formal peculiarities of the originals, but tries to preserve their inner content, naturalness and depth.
Keywords: taste, vernaculars, archaisms, style, folk flavour, text and subtext